Post-traumatic stress disorder, trauma and parenting stress: an individual participant data meta-analysis - Laurien Meijer; Kathleen Thomaes; Matthijs Blankers; Maja Deković; Molly R. Franz; Rolf Kleber; Elise M. van de Putte; Elisa van Ee; Elena Camisasca; Steffany J. Fredman; Dominik Moser; Larry L. Mullins; et al. (European Journal of Psychotraumatology)
Background: Parental post-traumatic stress disorder (PTSD) symptoms are associated with heightened parenting stress, but it is unknown whether this relation depends on the timing (childhood or adulthood) and type of trauma (interpersonal or non-interpersonal). In survivors of childhood interpersonal trauma, PTSD and parenting stress may be more strongly intertwined.Objective: This study examined whether the relation between parental PTSD and parenting stress is moderated by childhood interpersonal trauma. Findings are supplemented with information on the process of performing an individual participant data meta-analysis (IPDMA) and lessons learned.Methods: Using one-stage IPDMA, data from published studies and unpublished datasets were synthesized and analysed using multilevel linear regression.Results: Twelve datasets were included (N = 1249: 92.5% female, M age = 32.8 years, 53.8% ethnic minority). Significant and positive main effects of PTSD and childhood interpersonal trauma on parenting stress were consistently found across studies. A moderating effect of childhood interpersonal trauma on the relation between PTSD and parenting stress was not found, but this finding may be impacted by limited data coverage. The proportion of individual-level variance in parenting stress explained by the model with main and interaction effects while controlling for education level was small to medium (R2 = .12, p = .003).Conclusion: This study is the first to investigate relations among parental childhood interpersonal trauma, PTSD, and parenting stress across studies using IPDMA methodology. Despite limitations in data coverage, its findings demonstrated that links among childhood interpersonal trauma, PTSD, and parenting stress were robust across populations and settings. This implies PTSD symptom reduction may be beneficial in reducing parenting stress, regardless of whether the parent experienced childhood interpersonal trauma. Additionally, lessons learned and suggestions for how IPDMA can bring the field of trauma and PTSD research forward are presented.